Intranet and internet applications for librarians - Sehgal, R. I. (Ess Ess Publications, 2004)
Contents of material: A global warehouse of information. Three ways to connect to the internet. Usenet newsgroups. How to read newsgroups. Electronic libraries and publicaton. Internet libraries. Three things to know about chatting on the net. Internet terminology.